2018
DOI: 10.1096/fj.201800150rr
|View full text |Cite
|
Sign up to set email alerts
|

Episodic β‐cell death and dedifferentiation during diet‐induced obesity and dysglycemia in male mice

Abstract: Loss of functional islet β-cell mass through cellular death or dedifferentiation is thought to lead to dysglycemia during the progression from obesity to type 2 diabetes. To assess these processes in a mouse model of obesity, we performed measures of circulating cell-free differentially methylated insulin II ( Ins2) DNA as a biomarker of β-cell death and aldehyde dehydrogenase 1 family member A3 (ALDH1A3) and forkhead box 01 (Foxo1) immunostaining as markers of β-cell dedifferentiation. Eight-week-old, C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Our results confirmed that HFD triggered the dedifferentiation and adaptive proliferation of β-cells, as previously reported ( 24 , 28 , 29 ). In HFD-fed βVmat2KO islets, dedifferentiation and cell death in β-cells are accelerated compared with in controls, which seems to attribute to β-cell failure.…”
Section: Resultssupporting
confidence: 93%
“…Our results confirmed that HFD triggered the dedifferentiation and adaptive proliferation of β-cells, as previously reported ( 24 , 28 , 29 ). In HFD-fed βVmat2KO islets, dedifferentiation and cell death in β-cells are accelerated compared with in controls, which seems to attribute to β-cell failure.…”
Section: Resultssupporting
confidence: 93%
“…Given that all individuals are either obese or overweight, it is possible that the unmethylated INS signal might be arising from adipocyte turnover; however, the elevations in unmethylated CHTOP-817, assuming that they are arising from the same cell type, likely point to an islet cell origin. In a prior study using high-fat diet feeding in mice, we observed that overweight/obese mice exhibit periodic increases in unmethylated INS DNA, and that these elevations correlated with increases in β cell death, as verified by immunostaining of pancreas sections from these animals [30]. These data suggest that the elevated unmethylated INS and CHTOP-817 signal in our cohort of overweight/obese youth might be arising from death of islet cells, recognizing that our assay cannot definitively conclude the specific islet cell type giving rise to this signal.…”
Section: Discussionmentioning
confidence: 57%
“…First, our studies in humans utilized cross-sectional cohorts, and we cannot comment on the occurrence or the timing of islet cell death following initial islet assault during the progression from obesity to T2D or from antibody-negative FDR to T1D. Given the short (~90 min) half-life of DNA in the circulation [15], if β cell death was episodic during disease progression in humans (as we observed previously in mice [30]), signals corresponding to cell death could be missed depending on the timing of sampling. Additional studies measuring differentially methylated INS and CHTOP from longitudinal cohorts are needed to resolve this issue.…”
Section: Discussionmentioning
confidence: 98%
“…4,45 As ALDH1A3 expression is inhibited by Foxo1 activity in β-cells, ALDH1A3 increases as Foxo1 expression is lost in diabetic mice. 4,8,46,47 Follistatin gene delivery did not reduce the ALDH1A3 expression in insulin-positive islet cells, suggesting that combination treatment with other strategies that target the key transcriptional programs in β-cells may offer scope to enhance long-term β-cell functionality further. Our studies do not rule out the possibility that the increased numbers of insulin-positive cells after treatment may also in-part result from increased proliferation and/or reduced apoptosis of β-cells.…”
Section: Discussionmentioning
confidence: 99%